Naming as business strategy: an analysis of eponymy and debt contracting - Chen, Chen; Song, Michelle; Truong, Cameron; Zhang, Jin (Review of Accounting Studies, 2024)
Abstract This study proposes that naming a firm eponymously is a mechanism that small private firms can use to signal their superior financial performance and commitment to fulfill debt contract obligations. Using 621,614 small private firms in Europe over the period 2008–2018, we find that small private eponymous firms pay significantly lower interest on their debts and have more long-term debt than non-eponymous firms. Our findings are robust to various controls and placebo tests. Additional analyses show that eponymy lowers the cost of debt and facilitates long-term debt via reputation signaling and private information. We also document that the effect of eponymy on debt contracting is most pronounced when there is less financial development and when firms’ dependence on external financing is low, consistent with the idea that high-quality firms opt for eponymy when they consider less external financing.